Egregore: Cultural conceptions and collective advertising identities as a reference in the creation of advertising content in Colima, Mexico (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
The research explores the interaction between advertising and culture in Mexico, in Colima State, in the municipalities of Colima, Comala, and Villa de Álvarez. Through a qualitative approach that includes interviews with experts in advertising, history, and design, in addition to a documentary review, the study examines how advertising uses and distorts cultural elements. A questionnaire was applied to capture collective perceptions and identify the cultural elements most ingrained in the social consciousness of the area. The results confirm the existence of cultural symbols used in advertising, evidence their distortion, and offer new perspectives on cultural advertising in the Colima context. The study contributes to the United Nations' Sustainable Development Goal No. 8 by promoting economic and cultural growth through advertising that is conscious and respectful of local identities.
Keywords: Advertising; Culture; Egregore; Cultural Transformation; Advertising Elements